Use of the Technology Acceptance Model for Electronic Medical Records in Nursing Documentation: Scooping Review - Sari, Novita; Mediawati, Ati Surya; Yudianto, Kurniawan (Indonesian Journal of Global Health Research, 2024)
Digital transformation in the health sector, especially in health services, where previously health facilities used manual medical records, switched to electronic medical records. The Technology Acceptance Model is a framework used to understand how users accept and adopt technology, in this case electronic medical records. This study aims to identifyuse of the Technology Acceptance Model on nurses' acceptance of the implementation of electronic medical records. This study used the scooping review method. Literature searches were obtained through 3 databases, namely PubMed and CINAHL, as well as Google Scholar with the keywords: Technology Acceptance Model, Nursing Documentation, Electronic Medical Record's. Articles were extracted manually through tabulation and analyzed using a descriptive analysis approach. The publication period in the article search is the last 10 years (2014-2024). Collecting data used manual table. There were 8 articles included in this study, where the results of the scoping showed a significant relationship between perceived usefulness and perceived ease of use on nurses' acceptance of attitudes and attitudes had a strong influence on intentions to use electronic medical records. The importance of management support in preparing electronic medical records from their usefulness and ease of use in supporting nursing service activities in health facilities.